Cytotoxic and Antitumor Activity of some Coumarin Derivatives - Garro, Hugo Alejandro (2016)
Several natural and synthetic coumarins were assayed against different cancer cell lines. Four of them have shown cytotoxicity against a panel of three human solid tumor cell lines (HeLa, T-47D, and WiDr) and a clearly activity/hydrophobicity relationship. Compound 13 proved to be the most active product in all cell lines tested, with values of 8.0 (±0.38) μM against HeLa cells and also able to inhibit Taq DNA polymerase. This dual activity of 13 makes it a candidate to be considered as a "lead" compound in the search for novel antitumor drugs.